Optimisation model of micro grid dispatching for smart building cluster based on blockchain. Issue 2 (3rd April 2022) - Zhao, Sheng; Wu, Zhengtian
ABSTRACT: With the rapid development of Chinese economy, the problem of building energy consumption is becoming more prominent. The application of distributed energy brings new solutions for building energy conservation. However, the traditional centralised aggregator approach has many disadvantages. This paper proposes an autonomous decentralized dispatching framework based on blockchain technology. The participating nodes can transfer and record data to each other through the established P2P energy blockchain network. The simulation result shows that the decentralized micro grid dispatching approach proposed in this paper canreduce the cost of distributed energy dispatching.